1988
DOI: 10.1136/gut.29.2.218
|View full text |Cite
|
Sign up to set email alerts
|

Sigmoid motility in diverticular disease and the irritable bowel syndrome.

Abstract: Measurements of motility of the alimentary tract are important in the understanding of gut physiology and the mechanism of symptoms. While the oesophagus, stomach and small intestine are readily accessible by oral transtubation, this does not apply to the colon. Most of the published data on colonic intraluminal pressures (IP's) derive from tube assemblies, positioned in the bowel through a rigid sigmoidoscope. Consequently the more proximal parts of the large intestine, including the potentially very interest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
48
0
6

Year Published

1990
1990
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(56 citation statements)
references
References 13 publications
2
48
0
6
Order By: Relevance
“…Paradoxically, inflating a balloon in the colon of individuals with DD induces the musculature of the colonic wall to yield to the increasing luminal pressure more quickly than in controls [38,39] . In addition, these and later studies indicate increased colonic motility (as assessed by number and amplitude of bowel wall contractions) in the sigmoid colon of individuals with left-sided DD [40,41] , and also in the ascending colon of patients with right-sided diverticulosis [42] . These classical studies were generally performed with low numbers and failed to account for age, gender, physical activity or body fat percentage; the physiological observations were made under artificial conditions, i.e.…”
Section: Intra-luminal Pressure and Colonic Motilitymentioning
confidence: 99%
“…Paradoxically, inflating a balloon in the colon of individuals with DD induces the musculature of the colonic wall to yield to the increasing luminal pressure more quickly than in controls [38,39] . In addition, these and later studies indicate increased colonic motility (as assessed by number and amplitude of bowel wall contractions) in the sigmoid colon of individuals with left-sided DD [40,41] , and also in the ascending colon of patients with right-sided diverticulosis [42] . These classical studies were generally performed with low numbers and failed to account for age, gender, physical activity or body fat percentage; the physiological observations were made under artificial conditions, i.e.…”
Section: Intra-luminal Pressure and Colonic Motilitymentioning
confidence: 99%
“…Patients with abnormalities of colonic transit respond poorly to traditional oral pharmaceutical preparation after ARM [1][2][3][4] , and those with colonic inertia such as a redundant colon and colonic diverticula have impaired colon motility [23][24][25] . Arhan et al 26) reported that anal stenosis is associated with abnormal function of rectum and the anal sphincter.…”
Section: Results After Arm In Patients With the Other Causes Of Chronmentioning
confidence: 99%
“…Similar contrasting results were reported from myolectrical studies of the rectosigmoid area [52,53] . However, more recent studies, carried out in the true sigmoid and descending colon (and, therefore, investigating colonic segments actually bearing diverticula) are available, which showed an increased motor activity in such patients (both symptomatic and asymptomatic) with respect to controls [54,55] . This abnormal motility was reduced following surgery [56] .…”
Section: Colonic Motilitymentioning
confidence: 99%